The Effect of the Nurse's Role as an Educator on Adherence to Taking Medication for Hypertensive Patients at RSU Imelda Pekerja Indonesia in 2023 - Ritonga, Yuni Shanti; Silaban, Nataria Yanti; Ritonga, Lelli Nur (SEAN Institute, 2023)
Hypertension is Wrong One disease No contagious that can cause death . Disease This as the silent disease because sufferer No know that himself currently caught symptom hypertension . one _ condition absolute For can reach effectiveness therapy And increase quality life patient is compliance , meanwhile Disobedient patient in consuming drug is Wrong One factor main reason failure therapy . Role nurse as educator help patient increase knowledge about maintenance And action medical so that patient get information For increase obedience drug to hypertension . Objective in study This is analyze influence role nurse as educator to obedience drink drug on patient hypertension .Method study This is method quantitative with approach cross- sectional conducted pafa 73 respondents sufferer Hypertension at RSU Imelda Pekerja Indonesia. Method study This use Technique data collection is carried out with method provide instruments in the form of questionnaire role nurse And obedience drink drugs that are then tested use Mann-Whitney test . Results study This show role nurse as Educator at Home Sick General Imeld Medan Indonesian workers are good as many as 49 respondents (67.1%), and obedience drink drug on patient Hypertension at RSU Imelda Pekerja Indonesia Medan respondent the most obedience while 60 respondents (82.2%). From the results study This between role nurse with obedience drink drug on patient with hypertension is there is influence with value (p=0.002). Can concluded that there is influence between role nurse as educator with obedience drink medicine . So the more Good role nurse as educator the more obey patient in drink medicine .